Penentuan Menu Makanan Untuk Penderita Diabetes Menggunakan Metode Iterative Dichotomizer Tree (ID3) - Naufal Sakagraha Kuspinta; Agus Wahyu Widodo; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Diabates Mellitus (DM) is a metabolic disorder caused by several factors such as insulin deficiency or the inability of the body to utilize insulin. Most patients suffer from this disease due to heredity and unhealthy lifestyle. Diabetes Mellitus is also a chronic disease that became a public health problem in Indonesia. In the body of patients with DM, the inability to automatically adjust the sugar levels in the blood like a healthy person makes them suffering from diabetes. Significant increases in hyperglycemia or sugar levels are believed to increase along with digested consumption. Causes of food sources consumed. Iterative Dichotomizer Tree (ID3) is one of the methods. Subjects in this research is the application of data grouping by using Iterative Dichotomizer Tree (ID3) to classify diabetic food menu data. The dataset used in this study is sourced from Puskesmas Kendalsari Malang. The results of this study is a system capable of grouping food menu datasets for diabetics using the ID3 method. From the test conducted by the results of the testing of 80 data trainning dan 20 data testing is 75%.